The role of the amygdala in depression: a bibliometric analysis (2015–2024) - Li, Yuanyuan; Yang, Dengxian; Cao, Mengye; Dong, Lifang; Jin, Liuyin; Gao, Shugui (Frontiers in Psychiatry, 2025)
BackgroundDepression is a highly heterogeneous disorder with complex mechanisms. Given converging evidence implicating the amygdala in its pathophysiology, a systematic and quantitative synthesis is warranted to map the research landscape, hotspots, and emerging trends.ObjectiveTo systematically characterize the research landscape of depression–amygdala studies from 2015 to 2024 using bibliometric and visualization analyses, identify core hotspots and emerging themes, and track their evolution to inform subsequent mechanistic research and precision interventions.MethodsUsing data from the Web of Science Core Collection and Scopus (2015–2024), we conducted a bibliometric analysis of English-language publications on depression and the amygdala with Bibliometrix and VOSviewer. Publication trends, country and institutional contributions, highly cited papers, and keyword co-occurrence/clustering were analyzed to delineate the field’s structure and evolution.ResultsA total of 5,999 publications were included. Annual output increased steadily from 399 in 2015 to a peak of 831 in 2024. The United States (1,813, 30.2%), China (1,122, 18.7%), and Germany (357, 6.0%) were the top contributors. The ratio of multi-country publications (MCP) was highest for Germany (28.3%), followed by the United Kingdom (28.1%) and Canada (24.6%). At the institutional and journal levels, the University of California system, Harvard University, and Harvard Medical School ranked among the leading contributors. The international collaboration network exhibited a U.S.-centered structure, with frequent partnerships between the United States and China (n = 113), the United States and the United Kingdom (n = 86), and the United States and Germany (n = 81). Keyword co-occurrence and clustering analyses revealed four major thematic clusters: emotion regulation networks, biological signaling and regulation, developmental risk factors, and animal models. Overall, the field has evolved from region-specific studies toward network- and system-level integration, highlighting the amygdala’s pivotal role in the neurobiological mechanisms of depression and its potential as a candidate neuromarker.ConclusionBibliometric evidence indicates that research on depression–amygdala relationships is moving toward multi-dimensional and cross-disciplinary integration. The amygdala’s involvement in emotion regulation and early-life stress is increasingly recognized; alterations in its functional connectivity show promise as a neuromarker of depression, though clinical translation requires multi-center validation and standardized analytic workflows.